Retracted: Function Matching of Terminal Modules of Intelligent Furniture for Elderly Based on Wireless Sensor Network - Chengmin Zhou; Xin Luo; Ting Huang; Tao Zhou (IEEE Access)
As the aging problem continues to intensify, the number of empty-nest elderly groups increases. Taking the living needs of the elderly as the core, intelligent and innovative design of elderly bedroom furniture in the direction of old age has become a hot topic. Therefore, it is very necessary to actively carry out research on the function matching of smart adaptable furniture terminal modules based on wireless sensor networks. The purpose of this article is to discuss the research on the functional matching of smart adaptable furniture terminal modules based on wireless sensor networks. The research object is the smart system for nursing homes. The system uses ZigBee technology to complete the indoor wireless sensor network (WSN) layout and conducts fall test experiments, Power saving experiment, network performance experiment, observe its performance. The research results show that the number of frontal fall tests is 50, the number of alarms is 48, and the accuracy rate is 96%; the number of back fall tests is 50, the number of alarms is 48, and the accuracy rate is 100%; The accuracy rate is 100%; the number of right side fall tests is 50 times and the number of alarms is 50 times, and the accuracy rate is 100%. It can be seen from this that the research on the function matching of smart adaptable furniture terminal modules based on wireless sensor networks is of great significance for enhancing the well-being of the elderly.